The Effectiveness of Low-Intensity Red Laser for Activating a Bleaching Gel and Its Effect in Temperature of the Bleaching Gel and the Dental Pulp - Pleffken, Patricia Rondon [UNESP]; Borges, Alessandra Buhler [UNESP]; De Paiva Goncalves, Sergio Eduardo [UNESP]; Gomes Torres, Carlos Rocha [UNESP] (Wiley-Blackwell, 2012)
Statement of the Problem: The effectiveness of low-intensity red laser for activating a bleaching gel and its effect in pulp temperature was not investigated in dental literature. Purpose: The objective of this study was to assess the effectiveness of low-intensity red laser for activating a bleaching gel, as well as its effect in temperature of the bleaching gel and the dental pulp. Materials and Methods: Forty extracted bovine teeth were immersed in a solution of coffee 14 days for darkening. The initial colors were recorded by spectrophotometric analysis. The specimens were randomly distributed into two groups (N = 20): the control, which did not receive light and the experimental group that received light from an appliance fitted with three red light-emitting laser diodes (? = 660 nm). A green-colored, 35% H2O2based bleaching gel was applied for 30 minutes, and changed three times. After bleaching, the colors were again measured to obtain the L*a*b* values. Color variation was calculated (?E) and the data submitted to the non-paired t-test (5%). To assess temperature, 10 human incisors were prepared, in which one thermocouple was placed on the bleaching gel applied on the surface of the teeth and another inside the pulp chamber. Results: There was a significant difference between the groups (p = 0.016), and the experimental group presented a significantly higher mean variation (7.21 +/- 2.76) in comparison with the control group (5.37 +/- 1.76). There was an increase in pulp temperature, but it was not sufficient to cause damage to the pulp. Conclusion: Bleaching gel activation with low-intensity red laser was capable of increasing the effectiveness of bleaching treatment and did not increase pulp temperature to levels deleterious to the pulp. CLINICAL SIGNIFICANCE The application of a low-intensity red laser was effective for activating a bleaching gel with green dye, without any deleterious increases in pulpal temperature. (J Esthet Restor Dent 24:126134, 2012)